Internationalization of Tertiary Education in the Middle East and North Africa - World Bank (World Bank, Washington, DC, 2021)
Conceived in order to provide a crucial baseline in research on internationalization in MENA, this report draws on available data to respond to both a real need for regional analysis and a direct demand from stakeholders, including tertiary education institutions in the region. Encouraging internationalization to be mainstreamed throughout MENA is the objective that this report seeks to achieve by way of stimulating regional policy dialogue on the subject. The report presents some global trends in internationalization and details its main benefits, before providing an overview of the current status of internationalization in the MENA region, including an in-depth analysis of student mobility. In its reflections on the way forward for the region, the report situates its recommendations in the context of COVID-19, within which, despite serious challenges due to a lack of attractiveness of the region, MENA may find a key opportunity. It suggests that adapting to the “new normal” through the deeper implementation of internationalization “at home” – a dimension that does not require physical mobility and, being implemented within domestic environments, has a much wider reach – may help enable the region to make strides towards catching up on the internationalization agenda.